ASSESSMENT OF THE QUALITY OF ARABICA COFFEE BEANS FROM THREE PROCESSING METHODS AND TWO TYPES OF PACKAGING MATERIALS - Okky S. Dharmaputra; Santi Ambarwati; Ina Retnowati; Nijma Nurfadila (SEAMEO BIOTROP, 2021)
In Southeast Asia, Indonesia is the second highest-producing country of coffee beans after Vietnam. Consequently, Indonesia competes with other countries in producing good quality coffee beans. However, not many people have sufficient skills in tackling problems related to the postharvest handling of these coffee beans. The objective of this study was to assess the quality of Arabica coffee (Coffea arabica) beans in terms of moisture content, fungal infection (especially ochratoxin A or OTA producing fungi), OTA contamination, and the taste of the coffee during storage. The three processing methods used were dry, wet, and semi-wet methods. The beans were packed using two types of packaging materials, i.e. Kantong Semar high gas barrier and polypropylene bags (4 kg/bag). They were then stored under warehouse conditions during 4 months of storage. The moisture content of coffee beans processed using the three methods and packed using polypropylene bags was higher than that of coffee beans packed using Kantong Semar high gas barrier; however, it was still lower than the safe moisture content for coffee determined by the Indonesian National Standard (12.5%). Aspergillus niger was found in coffee processed using the three methods and packed using a Kantong Semar high gas barrier. Its population was relatively low (< 0.1 x 10 cfu/g wet basis). Aspergillus ochraceus was found in coffee processed using dry and wet methods at the beginning of storage. Its population was also relatively low (< 0.3 x 10 cfu/g w.b. OTA content was not detected in all coffee samples, because it was lower than the detection limit of the instrument used (< 1.85 ppb). At the beginning of the storage, all coffee samples were dominated by yeast with the population of 1.9 x 102 – 1.2 x 103 cfu/g w.b. The taste of coffee in various treatments during 4 months of storage was still above the total standard score for specialty grade ≥ 80. The highest total score (84) was found in coffee beans processed using a dry method and packed in Kantong Semar high gas barrier. The three processing methods and the two types of packaging materials can be used to maintain the quality of coffee beans during 4 months of storage.